Exploration of Understanding Attribution Communcation Theory Among Students of the State Islamic University of North Sumatera - Kartini Kartini; Syukur Kholil (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to explore the understanding of students of the State Islamic University (UIN) of North Sumatra towards the Theory of Attribution Communication and its implications for academic motivation and social interaction. Attribution Communication Theory is a theory that explains how individuals understand and interpret the causes of behavior, both from themselves and others. This study uses a qualitative method with a descriptive approach, where data is obtained through in-depth interviews with UIN North Sumatra students. The results of the study show that students generally understand the difference between internal attribution (personal factors) and external (external factors). Internal attribution is often used to describe academic success, which is associated with higher motivation to learn. In contrast, external attribution is more used to explain failures, which tend to lower motivation. In addition, the religiosity factor plays a significant role in the attribution process, where students often associate academic outcomes with God's will. This study emphasizes the importance of understanding attribution in shaping students' motivation and social interaction, and recommends increasing awareness of the role of attribution in learning and group dynamics in the educational environment